Comparison of Gene Expression Profiling in Sarcomas and Mesenchymal Stem Cells Identifies Tumorigenic Pathways in Chemically Induced Rat Sarcoma Model. (17th July 2012) - Honoki, Kanya; Fujii, Hiromasa; Tohma, Yasuaki; Tsujiuchi, Toshifumi; Kido, Akira; Tsukamoto, Shinji; Mori, Toshio; Tanaka, Yasuhito
Abstract : Mesenchymal stem cells (MSCs) are believed to be the cell of origin for most sarcomas including osteosarcoma and malignant fibrous histiocytoma (MFH/UPS). To identify the signaling pathways involved in sarcoma pathogenesis, we compared gene expression profiles in rat osteosarcoma and MFH cells with those in syngeneic rat MSCs. Analysis of genes that characterize MSCs such as CD44, CD105, CD73, and CD90 showed higher expression in MSCs compared to sarcomas. Pathways involved in focal and cell adhesion, cytokine-cytokine receptors, extracellular matrix receptors, chemokines, and Wnt signaling were down-regulated in both sarcomas. Meanwhile, DNA replication, cell cycle, mismatch repair, Hedgehog signaling, and metabolic pathways were upregulated in both sarcomas. Downregulation of p 21 C i p 1 and higher expression of CDK4-cyclinD1 and CDK2-cyclinE could accelerate cell cycle in sarcomas. The current study indicated that these rat sarcomas could be a good model for their human counterparts and will provide the further insights into the molecular pathways and mechanisms involved in sarcoma pathogenesis.